Peran Efikasi Diri dalam Meningkatkan Kinerja Pegawai pada Instansi Pendidikan Daerah - Santi Sundari; Trio Saputra (Jurnal Administrasi Politik dan Sosial, 2025)
This study aims to examine the role of self-efficacy among employees of the Bengkalis Regency Education Office. A quantitative descriptive research design was employed, involving 150 employees as research subjects selected through a non-probability sampling technique using a census approach. Data were collected using a self-efficacy scale developed based on Bandura’s theory, consisting of 30 items. The data were analyzed using descriptive quantitative analysis. The findings reveal that the overall level of self-efficacy among employees falls within the moderate category, with a percentage of 66.7%. Male employees demonstrate a high level of self-efficacy (73.1%), while female employees show a moderate level (82.5%). In terms of age, the highest number of employees with self-efficacy is found in the 40–50 age group, which is categorized as moderate, totaling 90 employees. These results indicate that self-efficacy plays a crucial role in shaping employee confidence and performance in public sector organizations. Future studies are recommended to incorporate additional variables to examine broader relationships and causal effects. Moreover, further research is encouraged to expand the research setting and explore employee self-efficacy more deeply across different institutional contexts